Eating habits, body weight, and insulin misuse. A longitudinal study of teenagers and young adults with type 1 diabetes. - Bryden, K; Neil, A; Mayou, R; Peveler, R; Fairburn, C; Dunger, D (1999)
OBJECTIVE: To examine disordered eating, insulin misuse, weight change, and their relationships with glycemic control and diabetic complications in adolescents with type 1 diabetes followed up over eight years. RESEARCH DESIGN AND METHODS: Of 76 adolescents (43 male, 33 female) with type 1 diabetes aged 11-18 years at the first assessment, 65 were interviewed as young adults (aged 20-28 years). Eating habits were assessed using a standardized Eating Disorder Examination. Height and weight were determined and BMI calculated. Three consecutive urine specimens were collected for measurement of albumin/creatinine ratio and other significant diabetic complications were recorded. Glycemic control was assessed by glycated hemoglobin. RESULTS: Weight and BMI increased from adolescence to young adulthood. Females were overweight as adolescents and both sexes were overweight as young adults. Concern over weight and shape increased significantly for both sexes from adolescence to young adulthood. This increase in concern was reflected in increased levels of dietary restraint. Features of disordered eating were apparent in females at both assessments, but no patients met the criteria for anorexia nervosa or bulimia nervosa at either assessment. A total of 10 (30%) females, but none of the males admitted underusing insulin to control weight. Five (45%) females with microvascular complications had intentionally misused insulin to prevent weight gain. CONCLUSIONS: An increase in BMI from adolescence to adulthood was associated with higher levels of concern over shape and weight and more intense dietary restraint, especially among females. Overt eating disorders were no more prevalent in these patients than in the general population, but milder forms of disordered eating were common and had implications for diabetes management. Insulin omission for weight control was frequent among females and may contribute to poor glycemic control and to risk of complications.